2006
DOI: 10.1037/0022-0167.53.1.15
|View full text |Cite
|
Sign up to set email alerts
|

European American therapist self-disclosure in cross-cultural counseling.

Abstract: Abstract:Eleven European American psychotherapists' use of self-disclosure in cross-cultural counseling was studied using consensual qualitative research. As reasons for self-disclosing, therapists reported the intent to enhance the counseling relationship, acknowledge the role of racism/oppression in clients' lives, and acknowledge their own racist/oppressive attitudes. Results indicated that therapists typically shared their reactions to clients' experiences of racism or oppression and that these self-disclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 36 publications
(68 reference statements)
1
28
0
Order By: Relevance
“…Over time, a body of literature addressing race‐specific counseling competencies has emerged to correct a history of racially biased diagnosis and treatment decisions and to reduce disparities in access and quality of mental health services for clients of color (Alamilla, Kim, Walker, & Sisson, 2017; Burkard, Knox, Groen, Perez, & Hess, 2006; Cook et al, 2014; Helms, Nicolas, & Green, 2010; Spanierman & Smith, 2017). Specific to training a predominantly White student‐counselor population (Council for Accreditation of Counseling and Related Educational Programs, 2015), educators have suggested the importance of developing White students’ racial identities (Helms, 1995; Malott et al, 2015; Smith & Redington, 2010).…”
Section: Race‐based Competenciesmentioning
confidence: 99%
“…Over time, a body of literature addressing race‐specific counseling competencies has emerged to correct a history of racially biased diagnosis and treatment decisions and to reduce disparities in access and quality of mental health services for clients of color (Alamilla, Kim, Walker, & Sisson, 2017; Burkard, Knox, Groen, Perez, & Hess, 2006; Cook et al, 2014; Helms, Nicolas, & Green, 2010; Spanierman & Smith, 2017). Specific to training a predominantly White student‐counselor population (Council for Accreditation of Counseling and Related Educational Programs, 2015), educators have suggested the importance of developing White students’ racial identities (Helms, 1995; Malott et al, 2015; Smith & Redington, 2010).…”
Section: Race‐based Competenciesmentioning
confidence: 99%
“…Findings from the study by Burkard et al (2006) also showed that therapists' self disclosure about their emotional reactions to clients' experiences of racism was an important element in bridging cross racially. While it is important not to convey shock at the existence of racism, since the client needs to know that the therapist is aware of racism as a reality, sharing feelings of anger or shock about the brazenness of a specific event when a client discloses an experience is valuable.…”
Section: How To Talk About Race and Racismmentioning
confidence: 81%
“…Burkard et al (2006) found that the therapeutic relationship directly benefits from the therapist's ability to self disclose around race and racism. Findings from their study indicate that treatment is enhanced when therapists disclose their own struggles with benefiting from a racist system, or acknowledge unintentional complicity.…”
Section: How To Talk About Race and Racismmentioning
confidence: 97%
See 1 more Smart Citation
“…Eda Goldstein (1994) highlights numerous circumstances, which particularly contraindicate the use of self-disclosure. How much and what information therapists reveal about themselves may also depend on the age group they work with (Gaines, 2003) or the clinical context (Burkard, Knox, Groen, & Hess, 2006;Gibson, 2012). Knox and Hill (2003) note that although therapists' selfdisclosure can significantly affect their patients and the therapeutic bond, it belongs to one of the rarest interventions.…”
Section: Self-disclosure In Psychotherapymentioning
confidence: 97%